Prelacteal feeding and associated factors in Ethiopia: systematic review and meta-analysis - Habtamu Temesgen; Ayenew Negesse; Wubetu Woyraw; Temesgen Getaneh; Molla Yigizaw (BMC, 2018)
Abstract Background Prelacteal feeding can be defined as giving any solid or liquid foods other than breast milk during the first three days after birth. It affects timely initiation of breastfeeding and exclusive breastfeeding practices. Even though the issue was investigated in Ethiopia, fragmented and inconsistent findings were reported. Therefore, the main objective of this meta-analysis was to estimate the pooled prevalence of prelacteal feeding and associated factors in Ethiopia. Methods The preferred reporting items for systematic reviews and meta-analyses guideline was followed. Articles were systematically searched through different searching mechanisms. Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument adapted for cross-sectional study design was used for quality assessment of each individual study. The total of 28 studies were included and analyzed. The random effect model was used to estimate the pooled prevalence; subgroup analysis and meta-regression were performed to identify the probable source of heterogeneity. Both Egger's, and Begg's test were used to check publication bias. The effects between associated factor variables, and prelacteal feeding practices were tested. Results A total of 492 studies were retrieved and 28 studies were included in the meta-analysis. The pooled prevalence of prelacteal feeding practice in Ethiopia was 25.29% (95% Confidence Interval [CI] 17.43, 33.15) with severe heterogeneity (I2 = 99.7, p < 0.001) and no publication bias. Antenatal care (Odds Ratio [OR] 0.25, 95% CI 0.09, 0.69), counselling on infant feeding (OR 0.37, 95% CI 0.22, 0.63), timely initiation of breastfeeding (OR 0.28, 95% CI 0.21, 0.38) and an urban residence (OR 0.47, 95% CI 0.26, 0.86) had lower odds, while home birth had higher odds (OR 3.93, 95% CI 2.17, 7.10) of prelacteal feeding in Ethiopia. Conclusions In Ethiopia, one in four children were given prelacteal foods. Mothers who gave birth at home are more prone to give prelacteal foods. Whereas, antenatal care, timely initiation of breastfeeding, counseling on infant feeding and an urban residence decreases prelacteal feeding practices in Ethiopia. Therefore, the government and health institutions should focus to increase maternal health service utilization and promote infant and young child feeding practices according to the guideline.